Aerosols in the E3SM Version 1: New Developments and Their Impacts on Radiative Forcing. (4th January 2020) - Wang, Hailong; Easter, Richard C.; Zhang, Rudong; Ma, Po‐Lun; Singh, Balwinder; Zhang, Kai; Ganguly, Dilip; Rasch, Philip J.; Burrows, Susannah M.; Ghan, Steven J.; Lou, Sijia; Qian, Yun; et al.
Abstract: The new Energy Exascale Earth System Model Version 1 (E3SMv1) developed for the U.S. Department of Energy has significant new treatments of aerosols and light‐absorbing snow impurities as well as their interactions with clouds and radiation. This study describes seven sets of new aerosol‐related treatments (involving emissions, new particle formation, aerosol transport, wet scavenging and resuspension, and snow radiative transfer) and examines how they affect global aerosols and radiative forcing in E3SMv1. Altogether, they give a reduced total aerosol radiative forcing (−1.6 W/m 2 ) and sensitivity in cloud liquid water to aerosols, but an increased sensitivity in cloud droplet size to aerosols. A new approach for H2 SO4 production and loss largely reduces a low bias in small particles concentrations and leads to substantial increases in cloud condensation nuclei concentrations and cloud radiative cooling. Emitting secondary organic aerosol precursor gases from elevated sources increases the column burden of secondary organic aerosol, contributing substantially to global clear‐sky aerosol radiative cooling (−0.15 out of −0.5 W/m 2 ). A new treatment of aerosol resuspension from evaporating precipitation, developed to remedy two shortcomings of the original treatment, produces a modest reduction in aerosols and cloud droplets; its impact depends strongly on the model physics and is much stronger in E3SM Version 0. New treatments of the mixing state and optical properties of snow impurities and snow grains introduce a positive present‐day shortwave radiative forcing (0.26 W/m 2 ), but changes in aerosol transport and wet removal processes also affect the concentration and radiative forcing of light‐absorbing impurities in snow/ice. Plain Language Summary: Aerosol and aerosol‐cloud interactions continue to be a major uncertainty in Earth system models, impeding their ability to reproduce the observed historical warming and to project changes in global climate and water cycle. The U.S. DOE Energy Exascale Earth System Model version 1 (E3SMv1), a state‐of‐the‐science Earth system model, was developed to use exascale computing to address the grand challenge of actionable predictions of variability and change in the Earth system critical to the energy sector. It has been publicly released with new treatments in many aspects, including substantial modifications to the physical treatments of aerosols in the atmosphere and light‐absorbing impurities in snow/ice, aimed at reducing some known biases or correcting model deficiencies in representing aerosols, their life cycle, and their impacts in various components of the Earth system. Compared to its predecessors (without the new treatments) and observations, E3SMv1 shows improvements in characterizing global distributions of aerosols and their radiative effects. We conduct sensitivity experiments to understand the impact of individual changes and provide guidance for future development of E3SM and other Earth system models. Key Points: A description and assessment of new aerosol treatments in the Energy Exascale Earth System Model Version 1 (E3SMv1) is provided Contributions to the total aerosol‐related radiative forcing by individual new treatments and different processes are quantified Some of the new treatments are found to depend on model physics and require further improvement for E3SM or other Earth system models